PENGARUH DEBT TO EQUITY RATIO DAN RETURN ON ASSETS TERHADAP HARGA SAHAM - Dede Suharna; Anisa Fajarwati (Universitas La Tansa Mashiro, 2018)
This study aims to determine whether there is an effect of debt to equity ratio, return on assets on stock prices in Food and Beverage companies listed on the Indonesia Stock Exchange in the period 2013-2017. In this study the method used is a quantitative method with a description approach. Data analysis techniques used are the classic assumption test, multiple linear regression analysis techniques, correlation analysis, coefficient of determination, hypothesis testing, and also use the help of the SPSS V20 program for windows. The population in this study is the Food and Beverage companies listed on the Indonesian Edek Exchange in the period 2013-2017. There are 18 population of companies and the sample in this study obtained as many as 6 companies, the sampling method is purposive sampling. The results of the t-test partially showed that the debt to equity ratio variable had no significant effect on stock prices and return on assets also had no significant effect on stock prices. Simultaneous F test results Debt to Equity and return on assets have no significant effect on stock prices on food and beverage companies listed on the Indonesia Stock Exchange (BEI) for the period 2013 - 2017.